The effects of randomized appearance of text chunks in nurse eLearning lessons - Belcher, Tracy George (Kansas State University, 2018)
Today, educators try to maximize eLearning effectiveness by using various methodologies to engage the learner and increase learning and recall. If educators want to be able to continue this process, new eLearning methodologies must be investigated. The aim of this study was to determine if the method in which lesson content is present can affect learning. To this end, the research question was as follows: What difference, if any, does the random placement of small paragraphs, chunks, of text make in recall and learning in eLearning lessons? The research question was answered through an experiment that entails assigning an eLearning lesson to participants. The participants were randomly divided into two groups (control and experimental). Based on their assignment, they were either presented information in static paragraphs of text centered on the eLearning screen (control), or presented with randomly placed chunks of text on each new eLearning lesson screen. Although the data analysis showed no significant difference in assessment scores for either group, there are suggestions for continued research on this topic. The importance and value of this educational medium requires the use of the best and most impactful methodologies to maximize attention, clarity, learning, and recall. More research needs to be conducted with varying forms of chunking with different populations using eye-tracking to ensure optimized educational endeavors.
Keywords: eLearning; Recall; Educational Leadership; Text chunking; Clinical education